The perception of meaningful work by employed and self-employed workers in the sphere of education - Krylova, Natalia (Intersections. East European Journal of Society and Politics, 2024)
The collection of studies on meaningful work is still quite fragmented and lacks resumptive theoretical models that can be applied to various employment statuses. This article examines the meaningful work phenomenon for both employed and self-employed workers using qualitative data. Drawing on 16 in-depth semi-structured interviews with school teachers and self-employed private tutors in Russia, the analysis demonstrates the nature of meaningful work constructed by employment status. Different institutional frameworks form institutional legitimacy, professional community, the final product of work and the prestige of occupation. The article’s primary theoretical contribution is the development of a theoretical model that describes the multifaceted and impermanent nature of meaningful work. The practical implications include the revelation of prominent differences among workers having different employment statuses, which is a solid foundation for future attempts in conducting quantitative research.